The submillimetre view of massive clusters at z ∼ 0.8–1.6. Issue 3 (3rd April 2019) - Cooke, E A; Smail, Ian; Stach, S M; Swinbank, A M; Bower, R G; Chen, Chian-Chou; Koyama, Y; Thomson, A P
ABSTRACT: We analyse 850 μ m continuum observations of eight massive X-ray-detected galaxy clusters at z ∼ 0.8–1.6 taken with SCUBA-2 on the James Clerk Maxwell Telescope. We find an average overdensity of 850-μ m-selected sources of a factor of 4 ± 2 per cluster within the central 1 Mpc compared to the field. We investigate the multiwavelength properties of these sources and identify 34 infrared counterparts to 26 SCUBA-2 sources. Their colours suggest that the majority of these counterparts are probable cluster members. We use the multiwavelength far-infrared photometry to measure the total luminosities and total cluster star formation rates demonstrating that they are roughly three orders of magnitude higher than local clusters. We predict the H -band luminosities of the descendants of our cluster submillimetre galaxies and find that their stellar luminosity distribution is consistent with that of passive elliptical galaxies in z ∼ 0 clusters. Together, the faded descendants of the passive cluster population already in place at z ∼ 1 and the cluster submillimetre galaxies are able to account for the total luminosity function of early-type cluster galaxies at z ∼ 0. This suggests that the majority of the luminous passive population in z ∼ 0 clusters is likely to have formed at z ≫ 1 through an extreme, dust-obscured starburst event.